THU0090 Prevalence and clinical phenotype of anti-carbamylated protein antibodies in palindromic rheumatism. (12th June 2018) - Castellanos-Moreira, R.; Cabrera-Villalba, S.; José Gomara, M.; Ruiz-Esquide, V.; Salvador, G.; Rodriguez-Garcia, S.D.C.; Camacho, O.; Ramírez, J.; Hernández, M.V.; Cuervo, A.; Gómez-Puerta, J.A.; Cañete, J.D.; et al.
Abstract : Background: Anti-carbamylated protein antibodies (anti-CarP) are a newly-identified antibody family present in the sera of rheumatoid arthritis (RA) patients whose specificity is close to that of ACPA but whose sensitivity is lower. Palindromic rheumatism (PR) is an intermittent form of arthritis that may progress to RA. Patients with PR may present the characteristic autoantibody profile seen in RA, even in the absence of evolution to RA. There are no studies on the presence of anti-CarP antibodies in PR. Objectives: To analyse the prevalence of anti-CarP in patients with PR and evaluate their clinical phenotype and relationship with ACPA. Methods: Patients diagnosed with PR attended by the Arthritis Unit, Rheumatology Service, Hospital Clínic of Barcelona were included according to the criteria of Guerne et al. Only patients considered as pure PR (patients without evidence of RA or other chronic rheumatic disease at the time of the first determination of anti-CarP) were analysed. An established RA control group was included. Anti-CarP were analysed by a home-made ELISA using a fibrin/chimeric filaggrin homocitrulinated peptide as antigen. IgG, IgA and IgM isotypes were measured. ACPA were analysed with a commercial CCP2 test. The clinical and therapeutic characteristics were compared according to anti-CarP positivity/negativity and to the clinical evolution, including the progression to RA during the follow-up. Results: Anti-CarP were analysed in 54 patients with pure PR and 53 RA patients. Anti-CarP were detected in 16.7% and 37.7% (p: NS) of patients with PR and RA, respectively. All PR patients positive for anti-CarP were ACPA positive and had higher ACPA titers. IgG was the predominant isotype (100%), only one patient presented IgA (11.1%) and none IgM. In the RA group, the percentages of IgG, IgA and IgM were 55%, 50% and 40%, respectively, in anti-CarP positive patients. More anti-CarP positive patients developed RA (33.3% vs. 13.6%), although the difference was not significant, during a mean follow-up of 3.8±1.1 years. Remission at the last follow-up visit was more frequent in patients who were anti-CarP negative (22% vs. 60.5% p<0.05). Anti-CarP positive patients were receiving DMARD more frequently than anti-CarP negative patients (100% vs. 60% p<0.05). Conclusions: This is the first study to demonstrate the presence of anti-CarP in patients with pure PR. Anti-CarP was associated with ACPA positivity and higher ACPA titers. Anti-CarP isotypes differed between PR and RA, with lower isotype use in PR. Anti-CarP positivity in PR patients could indicate a more refractory disease, with lower rates of remission and greater predisposition to evolve to RA. Acknowledgements: This study was supported by two awards granted by Hospital Clínic de Barcelona, Research, Innovation and Education Department (Sonia Cabrera-Villalba, Premi Fi de residencia: Emili Letang 052012; Raul Castellanos-Moreira, Premi Fi de residencia: Emili Letang 379_33_PFR_ 250760_2017). Disclosure of Interest: None declared